Record and ecology of Zadiprion howdeni (Hymenoptera: Diprionidae) in Ixltán de Juárez, Oaxaca - Aguirre-Hidalgo, Victor; Casasola-González, José Arturo; Alfonso-Corrado, Cecilia; Santiago-García, Elias; Clark-Tapia, Ricardo (Instituto de Ecología, A.C., 2020)
To provide strategies to control an unusual pine sawfly outbreak in Oaxaca, the objective of this study was to identify the species and estimate cocoon density and life cycle of the defoliator. For species identification, we followed the taxonomic classification developed by David R. Smith and coworkers, using adult female and male sawflies. Density was evaluated in 10 sites; on each site, one tree was selected at random. From this tree we defined 1 m2 sampling units at 1 m, 2 m and 3 m from the tree stem. We also proposed a general life cycle based on field data and cocoons kept at laboratory conditions. We identified the presence of Zadiprion howdeni as the invasive sawfly in the region. In Ixtlán, the average density of the cocoons was 37.92 ± 8.63 per m2, with significant differences between plots. No significant differences were found in the average density of the cocoons per m2, regarding tree distance. However, significant differences in cocoon’s numbers were observed between males and females per m2. The sawfly´s longest life cycle stage is as a cocoon and the most sensitive stage of life was the adult. Management strategies are provided for the different stages of sawflies. To consolidate these strategies, it is important to continue gathering basic knowledge of the biology and ecology of this defoliating species.